An Investigation into Heat Transfer Enhancement by Using Oscillating Fins - Ihsan Y. Hussain; Karima E. Amori; Dheya G. Mutasher (Journal of Engineering, 2023)
The present work describes numerical and experimental investigation of the heat transfer characteristics in a plate-fin, having built-in piezoelectric actuator mounted on the base plate (substrate). The geometrical configuration considered in the present work is representative of a single element of the plate-fin and triple fins. Air is taken as the working fluid. A performance data for a single rectangular fin and triple fins are provided for different frequency levels (5, 30 and 50HZ) , different input power (5,10,20,30,40 and 50W) and different inlet velocity (0.5, 1, 2, 3, 4, 5 and 6m/s) for the single rectangular fin and triple fins with and without oscillation. The investigation was also performed with different geometrical fin heights ( 50mm and 35mm) and distance between the fins (3mm and 6mm). It is observed that the heat transfer increases with the increase in the frequency and Reynolds number. It is further observed that triple fins with (height=50mm and distance between the fins=3mm) gives better enhancement as compared to other cases, The study shows that the piezoelectric actuator when mounted on the rectangular fins gives great promise for enhancing the heat transfer rate